Los saberes ancestrales en la gestión del riesgo de desastres naturales en comunidades rurales de la organización CODIAG del cantón Guaranda, periodo Mayo - septiembre de 2023. - Rea Cayambe, Angel Rodrigo (2023)
For generations, the communities in the study area have faced a series of natural phenomena that affect their well-being, food security and the sustainability of their agricultural practices. Natural phenomena, such as frost, volcanic ash fall and strong winds, have been constant factors in the lives of these communities. However, these events are not perceived as imminent threats, but rather as part of the environment that has been understood, respected and confronted with the wisdom of past generations. The central problem lies in the lack of recognition and valuation of this ancestral knowledge in current risk management and sustainability approaches. Adaptation and mitigation strategies often focus on technological solutions and approaches that are alien to local realities. The lack of integration of this local knowledge in risk management programs has led to the underutilization of natural resources and the constant vulnerability of these communities to natural phenomena. The general objective of this research is to analyze and document the ancestral knowledge that communities in the study area have developed over time to cope with natural phenomena. The specific objectives are: Identify the main natural phenomena affecting the communities in the study area. Document and analyze the ancestral knowledge transmitted from generation to generation to deal with these phenomena. Evaluate the effectiveness of practices based on ancestral knowledge in reducing risks and preserving agriculture, housing and community health. To provide recommendations for integrating ancestral knowledge into risk management and sustainability strategies in the study area. The results of this research have revealed a deep local knowledge about natural phenomena and the implementation of effective practices to face them. The communities have learned to prevent these events through natural signals and have developed specific techniques to protect their crops and homes. This ancestral knowledge has proven to be highly effective in preserving local resources and people's health. In conclusion, ancestral knowledge in the study area is a valuable resource that should be recognized, valued and, most importantly, integrated into risk management and sustainability strategies. The rich heritage of knowledge accumulated by these communities over generations is essential to strengthen community resilience and promote sustainability in a world facing increasing environmental challenges. Risk management must consider this heritage of local knowledge as an indispensable ally in building a safer and more sustainable future for communities in the study area. This research highlights the need to value and promote ancestral knowledge in risk management and sustainability, recognizing that the wisdom accumulated over time can be a fundamental resource for addressing current and future challenges in these communities. The next page and media will focus on the literature review that supports this assertion and provides additional evidence of the importance of ancestral knowledge in the management of natural phenomena